Analysis of the Implementation of the YESS (Youth Entrepreneurship and Employment Support Services) Program for Chrysanthemum Farmers - Pandu Dewa Dana; Teguh Soedarto; Hamidah Hendrarini (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2025)
This study employed a saturation sampling method with 11 chrysanthemum farmers who participated in the YESS program in Tutur subdistrict, Pasuruan regency. Primary data was obtained through questionnaires and interviews regarding program implementation and benefits, while secondary data was obtained from relevant agencies. Data was collected through observations, interviews, and questionnaires using a Likert scale to measure perceptions and program benefits. Descriptive quantitative methods were used to analyze the implementation and socioeconomic benefits of the YESS program. The study aimed to understand the program's implementation, social and economic benefits, and the challenges faced by farmers. The results showed that the program improved farmers' skills, market access, and income. However, challenges such as distributing high-quality seeds and reducing losses still exist. The program positively impacts farmers' social and economic well-being. Recommendations focused on improving access to capital, modernizing agricultural facilities, and fostering collaboration to ensure the program's sustainability.